Strategic Partnership Management in Statistical Operations: A Case Study of Indonesia’s Central Bureau of Statistics (BPS) - Adibrata, Risky Habib; Maani, Karjuni Dt (Journal of Educational Management Research, 2025)
This study aims to analyze strategic management in the management of statistical partners at the BPS Office in Padang Panjang City based on four main management functions: planning, organizing, implementing, and supervising. The main problems in partner management include a rushed recruitment process, incomplete training, limited field supervision, and the lack of routine evaluation. This study used a descriptive qualitative method with interviews with key informants, such as BPS officials and statistical partners. The results showed that in terms of planning, the implementation of an annual recruitment system was considered more efficient, although the selection process was not optimal. The management team has been organized, but is still hampered by workload and a lack of human resources. The implementation of tasks by partners refers to an annual contract, but there are still disparities in quality and work motivation. Supervision is not optimal due to the limited number of field supervisors. Internal and external factors such as a lack of BPS human resources and low public trust. Therefore, a comprehensive improvement in management strategy is needed so that the management of statistical partners can run more effectively and sustainably.